Mediation and Moderation of Islamic Religiosity and Financial Risk Tolerance - Wulandari, Fitri; Andraeny, Dita (Journal of Finance and Islamic Banking, 2023)
This study investigates the mediation and moderation effects of Islamic religiosity and financial risk tolerance on investment decisions. It addresses a gap in the literature by exploring how these factors influence investment behavior, particularly in the context of Islamic finance. The research sample comprises individuals who have invested in Sharia-compliant assets, such as stocks, Sukuk, or Sharia mutual funds, and fall within the age range of 18 to 39 years. Data analysis is conducted using Structural Equation Modeling (SEM) with AMOS 23. The findings reveal interesting insights. Firstly, the direct impact of financial literacy on investment decisions is found to be insignificant. Secondly, while the moderating role of Islamic religiosity does not strengthen the influence of financial literacy on investment decisions, financial risk tolerance emerges as a significant mediator between financial literacy and investment behavior. Moreover, financial risk tolerance is observed to have a direct impact on investment decisions and can moderate the influence of financial attitudes on these decisions. These results contribute to a better understanding of the dynamics shaping investment behavior in the realm of Islamic finance. It highlights the importance of considering religious beliefs and risk attitudes in investment decision-making processes, particularly among individuals adhering to Islamic principles.